A Simple LC-MS/MS Method for Determination of Magnolol in Rat Blood and its Application in a Pharmacokinetic Study - Li, H.; Wen, X-S.; Di, W. (Arzneimittelforschung, 2012)
A simple LC-MS/MS method was developed for determination and pharmacokinetic study of magnolol in rat blood. Blood sample pretreatment involved a one-step extraction with methanol of 100 µL blood. The chromatographic separation was carried out on a Agilent Zobax SB C18 column with a mobile phase consisting of acetonitrile-0.2% formic acid (55:45, v/v) at a flow rate of 0.3 mL/min. The detection was performed on a triple quadrupole tandem mass spectrometer by multiple reaction monitoring via electro spray ionization source with positive mode. A high throughput was achieved with a run time of 4 min per sample. The standard curve for magnolol was linear (r > 0.999) over the concentration range of 2–1 000 ng/mL, with a lower limit of quantification of 2 ng/mL. The intra- and inter-day precision (relative standard deviation) values were not higher than 12% and the accuracy (relative error) was <5% at three quality control levels. This simple, fast and highly sensitive method was fully validated and successfully applied to a clinical pharmacokinetic study of magnolol in rats after oral administration.
Keywords: magnolol; LC-MS/MS; pharmacokinetics